(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Production Workers Developmental Milieu (PWDM) is one of the important aspect and need to check for evaluate the productivity of the plant. Many managements and workers believes in it but ground reality needs to check the same. In this research responses of Production Workers Developmental Milieu (PWDM) at Plant Level from Managements perspective are compared with worker’s perspective. Responses collected from 248 production mangers and 361 production workers. Results reveled that Management’s perception and workers perceptions towards Production workers Developmental Milieu are not different.